Preparation Method of Grinding Aids for Sc / O-Doped Sulfide Solid Electrolytes
Through the preparation method of the abrasive agent for Sc/O doped sulfide solid electrolyte, the conductivity and safety of Li6PS5Cl type sulfide solid electrolyte is improved, and the problems of its sensitivity to moisture and poor interface compatibility are solved, thereby achieving higher ionic conductivity and longer battery life.
Patent Information
- Application Number
- CN202510106270.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-01-23
AI Technical Summary
Li6PS5Cl type sulfide solid electrolyte is sensitive to moisture in the air and has poor interface compatibility with the negative electrode, resulting in uneven deposition of lithium ions and easy formation of lithium dendrites, affecting the stability and safety of the battery.
Using the preparation method of a grinding aid for Sc/O doped sulfide solid electrolyte, the microstructure of the electrolyte of electrolyte is improved by mixing ethanolamine thioglycolate, 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane, 1-allyl-3-ethylimidazole hexafluorophosphate and potassium ethanol in a solvent to form a grinding aid, and added to the Sc/O doped sulfide solid electrolyte, the microstructure of the electrolyte is improved by ball milling and heat treatment.
It improves the conductivity and safety of electrolyte materials, improves the ionic conductivity and cyclic stability of the electrolyte, reduces the formation of lithium dendrites, extends the service life of the battery and reduces safety risks.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly relates to a preparation method of a grinding aid for Sc / O-doped sulfide solid electrolytes. Background Art
[0002] Due to their high ionic conductivity and excellent processability, sulfide solid electrolytes have become outstanding among many fast ion conductors. Among them, Li 6 PS 5 Cl-type sulfide solid electrolytes are gradually becoming the main choice for the commercialization route of sulfide solid batteries due to their relatively high ionic conductivity and price advantages. However, Li 6 PS 5 Cl-type sulfide solid electrolytes are extremely sensitive to moisture in the air and have poor interfacial compatibility with the negative electrode, which easily leads to uneven deposition of lithium ions and the formation of lithium dendrites at the interface. In severe cases, it will cause the failure of all-solid-state lithium metal batteries.
[0003] To improve the electrochemical performance of sulfide solid electrolytes, researchers have made many efforts. For example, the patent with the publication number CN115051027A discloses a lithium thioargentogermanate-type solid electrolyte containing an in-situ precipitated phase of lithium halide and its preparation method. This electrolyte is obtained by doping a lithium thioargentogermanate compound with a cation M, where the ionic radius of the cation M is larger than that of phosphorus. This electrolyte induces cations M with large ionic radii (specifically, it can be Al, Si, Sc, Y, Zr) to occupy the P position through high-energy ball milling to achieve P-site doping, forming a series of novel cation M-doped lithium thioargentogermanate sulfide electrolyte materials. Thereby, the uniform distribution of halogen X inside the grains is improved, and the formation of a LiX coating layer on the grain surface is avoided; metastable halogen X atoms in-situ precipitate LiX particles along with Li atoms and are dispersed at the grain boundaries, greatly inhibiting the deposition and growth of metallic lithium inside the electrolyte, significantly enhancing the ability to inhibit lithium dendrites, and enabling all-solid-state batteries to operate at high current densities.
[0004] References (Zhao Zheng-guang, Chen Zhen-ying, Zhai Guang-qun, et al. Preparation of Sc / O-doped sulfide solid electrolytes and performance of all-solid-state batteries [J]. Energy Storage Science and Technology, 2023, 12(8): 2412-2423.) disclose a series of modified sulfide solid electrolytes synthesized using rare earth element compound scandium oxide as a dopant. The results show that when the doping amount of scandium oxide is 0.04, Li 6.08 P 0.96 Sc 0.04 S 4.94 O 0.06 Cl sulfide solid electrolyte shows a relatively high ionic conductivity, which can reach 3.17×10-3 S / cm, and even after being exposed to air for 90 min, the electrolyte can still exhibit a good crystal structure and good all-solid-state battery cycling performance.
[0005] However, Li 6 PS 5 Cl-type sulfide solid electrolytes still have room for improvement in terms of ionic conductivity, cycling stability, and safety. SUMMARY OF THE INVENTION
[0006] To solve the above problems existing in the prior art, the present invention provides a preparation method of a grinding aid for Sc / O-doped sulfide solid electrolytes. Through this grinding aid, the microstructure of the electrolyte material can be improved, thereby enhancing the conductivity and safety of the electrolyte material.
[0007] To achieve the above object, according to one aspect of the present invention, there is provided a preparation method of a grinding aid for Sc / O-doped sulfide solid electrolytes. The steps of the method are as follows: Add mercaptoacetic acid ethanolamine ester (CAS: 126-97-6), 2-vinyl-5,5-dimethyl-1,3,2-dioxaborolane (CAS: 246869-22-7), 1-allyl-3-ethylimidazolium hexafluorophosphate (CAS: 861908-19-2), and potassium ethoxide (CAS: 917-58-8) to a solvent for mixing and reacting. After the reaction is completed, remove the solvent to obtain the grinding aid.
[0008] Reaction mechanism: Mercaptoacetic acid ethanolamine ester undergoes a thiol-ene addition reaction with 2-vinyl-5,5-dimethyl-1,3,2-dioxaborolane, and mercaptoacetic acid ethanolamine ester undergoes a thiol-ene addition reaction with 1-allyl-3-ethylimidazolium hexafluorophosphate, with potassium ethoxide as a catalyst.
[0009] Preferably, the mass ratio of mercaptoacetic acid ethanolamine ester, 2-vinyl-5,5-dimethyl-1,3,2-dioxaborolane, 1-allyl-3-ethylimidazolium hexafluorophosphate, and potassium ethoxide is: 8.28 - 16.57∶0.75 - 3∶0.84 - 15.68∶1.68 - 4.21.
[0010] Preferably, the solvent is DMF (N,N-dimethylformamide). Further preferably, the ratio of DMF to mercaptoacetic acid ethanolamine ester is 100 - 200 ml∶8.28 - 16.57 g.
[0011] Preferably, the reaction temperature is 50 - 70 °C, and the reaction time is 50 - 100 min.
[0012] Preferably, the method for removing the solvent is distillation.
[0013] To achieve the above object, according to another aspect of the present invention, there is provided a grinding aid for Sc / O-doped sulfide solid electrolytes prepared by the above preparation method.
[0014] To achieve the above object, according to another aspect of the present invention, there is provided a method for preparing Sc / O-doped sulfide solid electrolytes using the above grinding aid, the method comprising the following steps:
[0015] (1) Mix Li 2 S, P 2 S 5 , LiCl and Sc 2 O 3 uniformly, and perform ball milling treatment to obtain a powdery material;
[0016] (2) Press the powdery material obtained in step (1) into a tablet and vacuum seal it, then perform isothermal heat treatment to obtain a sheet-shaped sulfide solid electrolyte material;
[0017] (3) Cool the sheet-shaped sulfide solid electrolyte material obtained in step (2) to room temperature, add the grinding aid for Sc / O-doped sulfide solid electrolytes and grind it into a powdery form to obtain the Sc / O-doped sulfide solid electrolyte.
[0018] Preferably, in step (3), the added mass of the grinding aid for Sc / O-doped sulfide solid electrolytes is 0.96%-4.3% of the mass of the sulfide solid electrolyte material.
[0019] Preferably, in step (1), the molar ratio of Li 2 S, P 2 S 5 , LiCl and Sc 2 O 3 is 2.5-2.6∶0.4-0.5∶1∶0.01-0.03, the ball milling speed is set at 500-600 r / min, and the ball milling time is set at 15-20 h.
[0020] Preferably, in step (2), the powdery material obtained in step (1) is pressed into a 16-19 mm sheet material under a pressure of 500-800 Pa.
[0021] Preferably, in step (2), the process conditions of the isothermal heat treatment are: the heat treatment temperature is 500-600 °C, the heat treatment time is 5-10 h, and the heating and cooling rates are both 0.5 °C / min.
[0022] Preferably, in step (3), the grinding time is 10-20 min.
[0023] The beneficial effects of the present invention are as follows:
[0024] (1) As a component of the grinding aid, the borane functional group can interact with the sulfide solid electrolyte material through its unique chemical properties, improve the crystallinity or microstructure of the material, thereby promoting ion transport and increasing the ionic conductivity of the electrolyte;
[0025] (2) 1-Allyl-3-ethylimidazolium hexafluorophosphate can enhance the ion mobility during the reaction by providing additional charge carriers or changing the electronic structure of the material, thereby improving the overall conductivity of the electrolyte material;
[0026] (3) The use of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane and 1-allyl-3-ethylimidazolium hexafluorophosphate not only helps to improve the charge-discharge efficiency of the battery, but also can extend the service life of the battery and reduce the safety risk during battery use. Specific Embodiments
[0027] To further elaborate on the technical means and effects adopted by the present invention, the following examples and comparative examples are used to detail the specific embodiments and effects according to the present invention.
[0028] Example 1
[0029] A method for preparing a grinding aid for Sc / O-doped sulfide solid electrolyte is as follows:
[0030] 8.28 g of ethanolamine ester of mercaptoacetic acid, 0.75 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 0.84 g of 1-allyl-3-ethylimidazolium hexafluorophosphate and 1.68 g of potassium ethoxide are added to 100 ml of DMF, and then stirred at 50 °C for 50 min, and the DMF is removed by distillation to obtain the grinding aid.
[0031] The method for preparing Sc / O-doped sulfide solid electrolyte using the above grinding aid includes the following steps:
[0032] (1) Weigh 119.47 g of Li 2 S, 111.13 g of P 2 S 5 , 42.39 g of LiCl and 4.14 g of Sc 2 O 3 as starting materials in a glove box, mix them evenly in a zirconia ball milling tank, then take out the sealed zirconia ball milling tank from the glove box and fix it on a high-energy planetary ball mill for ball milling treatment. The ball milling speed is set to 600 r / min and the ball milling time is set to 20 h.
[0033] After the ball milling is completed, the ball milling jar is put back into the glove box, and the material is scraped off from the wall of the zirconia ball milling jar to obtain a relatively uniform powdery material. The obtained powdery material is pressed into a 16-mm disc under a pressure of 500 Pa, and then it is vacuum-sealed into a quartz tube. The quartz tube is placed in a muffle furnace for isothermal heat treatment. The process conditions for the isothermal heat treatment are as follows: the heating and cooling rates are both 0.5 °C / min, the heat treatment temperature is 600 °C, and the heat treatment time is 10 h.
[0034] After the temperature of the muffle furnace drops to room temperature, take out the quartz tube, take out the flaky material from the quartz tube in the glove box, that is, the sulfide solid electrolyte material, add 2.65 g of the above-mentioned grinding aid, and grind it with an agate mortar for 10 min. After the electrolyte material becomes powdery, put it into a bottle for use.
[0035] Electrochemical performance test: Use the obtained powdery sulfide solid electrolyte material above to assemble a lithium-lithium symmetric battery, and operate it under the critical current density (CCD) of 0.95 mA / cm 2 for the lithium-ion insertion / extraction cycle process, and the stable operation time is 255 h.
[0036] Example 2
[0037] A preparation method of a grinding aid for Sc / O-doped sulfide solid electrolyte is as follows:
[0038] Add 12.43 g of mercaptoacetic acid ethanolamine ester, 1.5 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 7.42 g of 1-allyl-3-ethylimidazolium hexafluorophosphate and 2.95 g of potassium ethoxide to 150 ml of DMF, and then stir at 60 °C for 75 min. Remove DMF by distillation to obtain the grinding aid.
[0039] The method for preparing Sc / O-doped sulfide solid electrolyte using the above grinding aid includes the following steps:
[0040] (1) Weigh 116.7 g of Li 2 S, 106.69 g of P 2 S 5 , 42.39 g of LiCl and 2.758 g of Sc 2 O 3 as starting materials, mix them evenly in a zirconia ball milling jar, and then take out the sealed zirconia ball milling jar from the glove box and fix it on a high-energy planetary ball mill for ball milling treatment. The ball milling speed is set at 550 r / min, and the ball milling time is set at 17 h.
[0041] (2)After the ball milling is completed, place the ball milling jar back into the glove box, scrape the material from the wall of the zirconia ball milling jar to obtain a relatively uniform powdery material. Press the obtained powdery material into a 18-mm disc under a pressure of 600 Pa, and then vacuum-seal it into a quartz tube. Place the quartz tube in a muffle furnace for isothermal heat treatment. The process conditions for the isothermal heat treatment are as follows: the heating and cooling rates are both 0.5 °C / min, the heat treatment temperature is 550 °C, and the heat treatment time is 7 h.
[0042] (3)After the temperature in the muffle furnace drops to room temperature, take out the quartz tube. Remove the flaky material from the quartz tube in the glove box, that is, the sulfide solid electrolyte material, add 5.3 g of the above-mentioned grinding aid, and grind it with an agate mortar for 15 min. After the electrolyte material becomes powdery, bottle it for use.
[0043] Perform electrochemical performance tests: Assemble a lithium-lithium symmetric battery using the obtained powdery sulfide solid electrolyte material, and operate it under a critical current density (CCD) of 0.95 mA / cm 2 for the lithium ion insertion / extraction cycle process, and the stable operation time is 315 h.
[0044] Example 3
[0045] A preparation method of a grinding aid for Sc / O-doped sulfide solid electrolyte is as follows:
[0046] Add 16.57 g of mercaptoacetic acid ethanolamine ester, 3 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 15.68 g of 1-allyl-3-ethylimidazolium hexafluorophosphate, and 4.21 g of potassium ethoxide to 200 ml of DMF, stir at 70 °C for 100 min, and distill off DMF to obtain the grinding aid.
[0047] The method for preparing Sc / O-doped sulfide solid electrolyte using the above grinding aid includes the following steps:
[0048] (1)Weigh 114.9 g of Li 2 S, 88.9 g of P 2 S 5 , 42.39 g of LiCl, and 1.379 g of Sc 2 O 3 in the glove box as starting materials, mix them evenly in a zirconia ball milling jar, and then take out the sealed zirconia ball milling jar from the glove box and fix it on a high-energy planetary ball mill for ball milling. Set the ball milling speed to 500 r / min and the ball milling time to 15 h.
[0049] (2) After the ball milling is completed, place the ball milling jar back into the glove box, scrape the material from the wall of the zirconia ball milling jar to obtain a relatively uniform powdery material. Press the obtained powdery material into a 19-mm disc under a pressure of 800 Pa, and then vacuum-seal it into a quartz tube. Place the quartz tube in a muffle furnace for isothermal heat treatment. The process conditions for the isothermal heat treatment are as follows: the heating and cooling rates are both 0.5 °C / min, the heat treatment temperature is 500 °C, and the heat treatment time is 5 h.
[0050] (3) After the temperature of the muffle furnace drops to room temperature, take out the quartz tube, take out the flaky material from the quartz tube in the glove box, which is the sulfide solid electrolyte material, add 10.6 g of the above-mentioned grinding aid, and grind it with an agate mortar for 20 min. After the electrolyte material becomes powdery, bottle it for use.
[0051] Electrochemical performance test: Assemble a lithium-lithium symmetric battery using the obtained powdery sulfide solid electrolyte material, and operate it under the critical current density (CCD) of 0.95 mA / cm 2 for the lithium-ion insertion / extraction cycle process, and the stable operation time is 322 h.
[0052] Comparative Example 1
[0053] The difference between this comparative example and Example 1: In step (3) of preparing the Sc / O-doped sulfide solid electrolyte, no grinding aid is added, and the flaky sulfide solid electrolyte material is ground with an agate mortar for 15 min to obtain a powdery electrolyte material.
[0054] Electrochemical performance test: Assemble a lithium-lithium symmetric battery using the obtained powdery sulfide solid electrolyte material, and operate it under the critical current density (CCD) of 0.95 mA / cm 2 for the lithium-ion insertion / extraction cycle process, and the stable operation time is 100 h.
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 1: The grinding aid does not contain ionic liquid, and the others are the same as in Example 1.
[0057] A preparation method of a grinding aid for Sc / O-doped sulfide solid electrolyte is as follows:
[0058] Add 12.43 g of mercaptoacetic acid ethanolamine ester, 1.5 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, and 2.95 g of potassium ethanolate to 150 ml of DMF, and then stir at 60 °C for 75 min. Remove DMF by distillation to obtain the grinding aid.
[0059] Perform electrochemical performance tests: Assemble the obtained powdery sulfide solid electrolyte material above to obtain a lithium-lithium symmetric battery, and operate it under the critical current density (CCD) of 0.95 mA / cm 2 during the lithium-ion insertion / extraction cycle process. The stable operation time can be 224 h.
Claims
1. A method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte, characterized in that: include: Thioglycolic acid ethanolamine ester, 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 1-allyl-3-ethylimidazolium hexafluorophosphate and potassium ethoxide are mixed and reacted in a solvent, and thioglycolic acid ethanolamine ester and 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane undergo a thiol-alkenyl addition reaction, and thioglycolic acid ethanolamine ester and 1-allyl-3-ethylimidazolium hexafluorophosphate undergo a thiol-alkenyl addition reaction. After the reaction is completed, the solvent is removed to obtain the grinding aid for the Sc / O doped sulfide solid electrolyte.
2. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The mass ratio of thioglycolate ethanolamine, 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 1-allyl-3-ethylimidazole hexafluorophosphate and potassium ethoxide is: 8.28-16.57∶0.75-3∶0.84-15.68∶1.68-4.21。 3. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The solvent is DMF.
4. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The reaction temperature is 50-70 ℃, and the reaction time is 50-100 min.
5. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The method for removing the solvent is distillation.
6. A grinding aid for Sc / O-doped sulfide solid electrolyte prepared by the preparation method according to any one of claims 1 to 5.
7. A method for preparing a Sc / O-doped sulfide solid electrolyte using the grinding aid for Sc / O-doped sulfide solid electrolyte according to claim 6, characterized in that: The following steps are involved: (1) Li2S, P2S5, LiCl and Sc2O3 are mixed evenly and ball-milled to obtain a powdery material; (2) The powdered material obtained in step (1) is pressed into a sheet, vacuum-sealed, and then subjected to a constant temperature heat treatment to obtain a sheet-like sulfide solid electrolyte material; (3) The flaky sulfide solid electrolyte material of step (2) is cooled to room temperature, and the Sc / O-doped sulfide solid electrolyte grinding aid is added thereto and ground into powder to obtain the Sc / O-doped sulfide solid electrolyte.
8. The method for preparing a Sc / O-doped sulfide solid electrolyte according to claim 7, characterized in that: In step (3), the added mass of the grinding aid for the Sc / O-doped sulfide solid electrolyte is 0.96%-4.3% of the mass of the Sc / O-doped sulfide solid electrolyte material.
9. The method for preparing Sc / O doped sulfide solid electrolyte according to claim 7, characterized in that: In step (1), the molar ratio of Li2S, P2S5, LiCl and Sc2O3 is 2.5-2.6:0.4-0.5:1:0.01-0.03, the ball milling speed is set to 500-600 r / min, and the ball milling time is set to 15-20 h.
10. The method for preparing Sc / O doped sulfide solid electrolyte according to claim 7, characterized in that: In step (2), the process conditions of the constant temperature heat treatment are: the heat treatment temperature is 500-600 °C, the heat treatment time is 5-10 h, and the heating and cooling rates are both 0.5 °C / min.
Citation Information
Patent Citations
Lithium argyrodite type solid electrolyte containing lithium halide in-situ precipitated phase as well as preparation method and application of lithium argyrodite type solid electrolyte
CN115051027A
Preparation method of compound with optical activity
CN102050820A
Polymer solid-state electrolyte material and preparation method therefor
CN107069081A